Immune Reconstitution of Patients Who Recovered From Steroid-Refractory Acute Graft-Versus-Host Disease After Basiliximab Treatment - Deng, Dao-Xing; Fan, Shuang; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; Pei, Xu-Ying; et al. (Frontiers in Oncology, 2022)
We aimed to identify the characteristics of Immune reconstitution (IR) in patients who recovered from steroid-refractory acute graft-versus-host disease (SR-aGVHD) after basiliximab treatment. A total of 179, 124, 80 and 92 patients were included in the analysis for IR at 3, 6, 9, and 12 months, respectively, after haploidentical donor hematopoietic stem cell transplantation (HID HSCT). We observed that IR was fastest for monocytes and CD8+ T cells, followed by lymphocytes, CD3+ T cells, and CD19+ B cells, and slowest for CD4+ T cells. Almost all immune cell subsets recovered comparably between patients receiving < 5 doses and ≥ 5 doses of basiliximab. Most immune cell subsets recovered comparably between SR-aGVHD patients who recovered after basiliximab treatment and event-free HID HSCT recipients. Patients who recovered from SR-aGVHD after basiliximab treatment experienced satisfactory IR, which suggested that basiliximab may not have prolonged negative impact on IR of these patients.